FORMULATION AND EVALUATION OF SUMATRIPTAN IMMEDIATE RELEASE TABLETS - Munija, P; Srikanth, G (Journal of Drug Delivery and Therapeutics, 2018)
The rationale of this investigation is to design an immediate release oral dosage of Sumatriptan succinate by using microcrystalline cellulose as filler, camphor and menthol as subliming agents by direct compression method .The basic objective of this dissertation is to develop an orodispersible tablet of sumatriptan succinate used in anti-migraine with an aim of reduces the lag time and providing faster onset of action to relief the acute migraine effect immediately. Disintegrates and disperses in oral cavity within 30 seconds without the need of drinking water. Has pleasant mouth feel and there is no after taste or grittiness. Successfully discriminates the ability of three superdisintegrants to promote drug dissolution and proposes a model formulation for disintegrants performance testing and quality control purposes. The formulation F6 containing 8% of CCS and 10% of menthol showed disintegration time of 18seconds after drying. Menthol as subliming agent was found to be most effective of all other subliming agents as it had showed drastic effect on the drug release.Keywords: Sumatriptan succinate, sublimation, menthol, anti-migraine